2008
DOI: 10.2353/ajpath.2008.071039
|View full text |Cite
|
Sign up to set email alerts
|

Sall1, Sall2, and Sall4 Are Required for Neural Tube Closure in Mice

Abstract: Four homologs to the Drosophila homeotic gene spalt (sal) exist in both humans and mice (SALL1 to SALL4/Sall1 to Sall4, respectively). Mutations in both SALL1 and SALL4 result in the autosomal-dominant developmental disorders Townes-Brocks and Okihiro syndrome, respectively. In contrast, no human diseases have been associated with SALL2 to date, and Sall2-deficient mice have shown no apparent abnormal phenotype. We generated mice deficient in Sall2 and, contrary to previous reports, 11% of our Sall2-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 40 publications
5
52
0
Order By: Relevance
“…Bohm et al reported that Sall2 knockout mice present strain-dependent neural tube defects (NTD) [4]. In agreement with this and our study, a decrease on SALL2 expression has been linked to neural tube defects induced by valproic acid [5].…”
Section: Introductionsupporting
confidence: 90%
“…Bohm et al reported that Sall2 knockout mice present strain-dependent neural tube defects (NTD) [4]. In agreement with this and our study, a decrease on SALL2 expression has been linked to neural tube defects induced by valproic acid [5].…”
Section: Introductionsupporting
confidence: 90%
“…Many of these genes are involved in neurodevelopment and neurogenesis. These include CNP 52 , EN1 45 , ROBO3 53 , ZNRF2 54 , NEUROD1 55 , BMP2 56 , FGF18 57 , SALL1 58 , TULP3 59 , PTEN 60 , ILK 61 , TSC2 62 , CALD1 63 , HOXA3 64 , UTRN 65 , NTF3 66 and EPHB2 67 , among others. Further, additional genes were associated with the development of or risk for various neurological disorders, including autism ( ROBO3 53 , SYN3 and GRIK4 68 ), attention deficit hyperactivity disorder ( ISL1 69 ), Tourette’s syndrome ( SLITRK1 70 ), schizophrenia ( NEUROD1 55 and CYFIP1 71 ), and Alzheimer’s disease ( NQO1 72 and FKBP1B 73 ).…”
Section: 1 Discussionmentioning
confidence: 99%
“…Surprisingly, genes previously considered as neural crest specifiers like FoxD3 and N-myc are transiently coexpressed with pre-neural transcripts before being confined to the neural crest domain (Khudyakov and Bronner-Fraser, 2009) suggesting that at early stages a common regulatory state may define progenitors for both lineages. In addition to Pea3, the Ets transcription factor Erm is now also present in the forming neural plate and the surrounding ectoderm (Lunn et al, 2007) as are Zic1-5 (Elms et al, 2004;Elms et al, 2003;Gamse and Sive, 2001;Inoue et al, 2007;Merzdorf, 2007;Mizuseki et al, 1998;Nakata et al, 1997Nakata et al, , 1998, Dlx3 (in chick; Khudyakov and Bronner-Fraser, 2009), Sall1 (Bohm et al, 2008;Sweetman et al, 2005) and Spalt4 (or Sall4; Barembaum and Bronner-Fraser, 2007). In Xenopus, Zic1 and Zic5 are activated at the edge of the neural plate in response to FGF signalling presumably from the underlying paraxial mesoderm (Hong and Saint-Jeannet, 2007;Monsoro-Burq et al, 2003); in tissue recombination assays paraxial mesoderm can induce Zic5 in animal caps, but this is blocked in caps injected with dominant negative FGF receptor (Monsoro-Burq et al, 2003).…”
Section: Subdivision Of the Ectoderm By Sequential Activation Of Tranmentioning
confidence: 96%